REFLECTION OF HUMOR IN MEDIA ACTIVITY IN UZBEKISTAN AND THE PROBLEMS OF DEVELOPING YOUTH ARTISTIC AND AESTHETIC CULTURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article aims to reflect the ridiculousness of the mass media in Uzbekistan and the problems of developing the artistic and aesthetic culture of young people, as well as to further improve the media activity of Uzbekistan, which is taking a bold step towards national revival and national growth, and to implement the necessary reforms in its field. . Art, which is the result of human cognitive activity, essentially reflects a certain ideology.